Evaluation of the corrosion resistance of steel elements from electrolytic refining plant - Stefanović Jelena; Avramović Zoran; Dimitrijević Silvana; Đorđević Jelena; Živanović Miloš; Jovanović Nikola (Mining and Metallurgy Engineering Bor, 2025)
The aim of this paper is to present a method for determine a model for accelerated corrosion testing of S235 steel. The experiment was conducted in two parts. In the first part, steel specimens were placed in the Electrolytic Refining Plant, in real conditions, in a indoor. This part of the experiment lasted 6 months. In the second part of the experiment, an attempt was made to obtain a model for accelerated corrosion testing that would accurately simulate real conditions in the Electrolysis. The steel specimens were therefore immersed in the electrolyte solution from the Electrolysis for a month. After cleaning the specimens, mass loss measurements were performed, and then these values were used to determine the corrosion rate after extended exposure. The results show that a shorter experimental duration should be chosen for specimens immersed in the electrolyte solution.